معوقات إستخدام التعليم المدمج في الدراسات العليا التربوية بجامعة القاهرة من وجهة نظر أعضاء هيئة التدريس - شعبان، أماني عبدالقادر محمد (جامعة المنوفية - كلية التربية, 2018)
هدفت الدراسة إلى التعرف على مفهوم التعليم المدمج، وأهميته، ومميزاته، ومبررات استخدامه بالجامعات، ومتطلباته، ومعوقاته، والتعرف على واقع التعليم المدمج في الدراسات العليا التربوية بجامعة القاهرة، والكشف عن المعوقات التي تحد من استخدام التعليم المدمج في الدراسات العليا التربوية بجامعة القاهرة من وجهة نظر أعضاء هيئة التدريس، وصياغة بعض المقترحات التي قد تسهم في تفعيل استخدام التعليم المدمج في الدراسات العليا التربوية بجامعة القاهرة. واستخدمت الباحثة المنهج الوصفي مستعينة بأداة الإستبانة وطبقت على عينة قوامها (51) من أعضاء هيئة التدريس بكلية الدراسات العليا للتربية بجامعة القاهرة. وتوصلت الدراسة إلى أن هناك معوقات تعوق استخدام التعليم المدمج في الدراسات العليا التربوية بجامعة القاهرة بدرجة كبيرة، وتأتي المعوقات المتعلقة بالبنية التحتية في المرتبة الأولى، والمعوقات المتعلقة بأعضاء هيئة التدريس في المرتبة الثانية، والمعوقات المتعلقة بالمنهج في المرتبة الثالثة، والمعوقات المتعلقة بالطلبة في المرتبة الرابعة. كما توصلت الدراسة إلى بعض المقترحات التي قد تسهم في تفعيل استخدام التعليم المدمج في الدراسات العليا التربوية ومنها: توفير بنية تحتية على أعلى كفاءة من التقنيات التكنولوجية، وتهيئة الطلاب لتقبل التعليم المدمج، وتدريبهم على استخدام منظومة التعليم المدمج، ونشر ثقافة التعليم المدمج بين أعضاء هيئة التدريس، وتدريبهم على إعداد المقررات الإلكترونية.
The study aimed to identify the concept of Blended Learning, its importance, its advantages, the reasons for its use in universities, its requirements and its obstacles, and the recognition of the reality of the Blended Learning in the postgraduate educational studies at Cairo University, and the detection of obstacles that limit the use of Blended Learning in postgraduate educational studies at Cairo University from the point of view of the members of the faculty and formulated some proposals that may contribute to the activation of the use of the Blended Learning in the postgraduate educational studies at Cairo University. The researcher used the descriptive approach using the questionnaire tool and applied to a sample of (51) faculty members at the Faculty of Post¬-graduate Studies of Education, Cairo University. The study found that there are obstacles that hinder the use of Blended Learning in the postgraduate educational studies at Cairo University to a large extent. The obstacles related to infrastructure are ranked first, the obstacles related to the faculty members are ranked second, the obstacles related to the curriculum are ranked third and the obstacles related to students are ranked fourth. The study also reached some suggestions that may contribute to the activation of the use of Blended Learning in the postgraduate educational studies, including: Providing the infrastructure with the highest level of technological technology, preparing students to accept Blended Learning, training them to use the Blended Learning system, Teaching, and training in the preparation of electronic courses.
Keywords: السياسة التعليمية -- البرامج التعليمية -- الوسائل التعليمية -- التعليم المدمج -- التعليم الجامعي -- طلاب الجامعات -- جامعة القاهرة -- كلية الدراسات العليا -- مصر -- أعضاء هيئة التدريس